Transcriptomic and metabolomic insights into the synergistic effects of resveratrol and β-hydroxy-β-methylbutyric acid on hepatic function under varying protein diets in Tibetan sheep - Yu Zhang; Kaina Zhu; Fengshuo Zhang; Zhenling Wu; Shengzhen Hou; Linsheng Gui (Frontiers in Nutrition, 2025)
BackgroundIncreasing evidence indicated resveratrol (RES) and β-hydroxy-β-methylbutyric acid (HMB) regulated several biological processes via modulating gene expression. This study employed transcriptomic and metabolomic analyses to investigate the impact of RES and HMB supplementation, in combination with varying dietary protein levels on hepatic immunity, antioxidant capacity, and morphology in Tibetan sheep.MethodsTwo treatments (with or without RES and HMB supplementation) and two dietary protein levels (12% vs. 14% of the basal diet) were tested according to a 2 × 2 factorial arrangement within a Latin square design. A total of 120 healthy two-month-old male Tibetan lambs (16.87 ± 0.31 kg) were randomly allocated for 90-day feeding experiment, with the following treatments: low-protein basal diet without (L group) or with (L-RES + HMB group) supplemental 1.50 g/d RES and 1.25 g/d HMB, and high-protein basal diet without (H group) or with (H-RES + HMB group) supplemental 1.50 g/d RES and 1.25 g/d HMB.ResultsThe results indicated that the liver tissue structure was predominantly normal in the H-RES + HMB group, devoid of central vein congestion. The catalase (CAT) activity and total antioxidant (T-AOC) capacity were significantly increased when fed the 14% protein diet (p < 0.05). The superoxide dismutase (SOD) and CAT activities of sheep fed supplementary-treated diets were significantly increased than the basal diet (p < 0.05). Immunoglobulin M (IgM) level and tumor necrosis factor-alpha (TNF-α) activity in the H-RES + HMB group were significantly increased than those in the H and L groups (p < 0.05), whereas interleukin-1 beta (IL-1β) levels were significantly lower (p < 0.05). A total of 4,236 differentially expressed genes (DEGs) were identified, including 3,503 upregulated genes and 733 downregulated genes, which were categorized into immune-related KEGG signaling pathways. Metabolomic analysis identified that compared to L group, the abundance of 918 metabolites were significantly changed in H-RES + HMB group including 829 upregulated and 89 downregulated. Those differential metabolites enriched in KEGG pathways primarily related to immunity and antioxidation.ConclusionDietary protein level and RES/HMB supplementation exhibited positively interaction effect on immunity and antioxidant capacity. The 14% protein diet with RES and HMB improved the hepatic function through modulating the gene and metabolite in Tibetan sheep.